The Effectiveness of Herbicide Use in Weed Control in Oil Palm Plantation Plate Areas - Humairo Aziza; Emi Malaysia; Agustina Wati Lestari; Sri Ngapiyatun (Jurusan Pertanian Politeknik Pertanian Negeri Samarinda Kampus Sei Keledang Jalan Samratulangi, Kotak Pos 192 Samarinda 75123, 2024)
The existence of weeds on agricultural land causes competition with cultivated plants in obtaining nutrients, water, and sunlight. Therefore, it is necessary to carry out weed control so as not to interfere with the growth and development of cultivated plants. This study aims to find out the types of weeds that grow in the disc area and to find out the most effective herbicides based on the content of active ingredients in controlling weeds in the oil palm disc area. Sampling was carried out by purposive sampling technique. Based on this technique, 2 blocks were obtained as research locations, namely block 73B and block 68A with a sample area of 351 m2 in each block. In this area, 9 sample plots were made with the size of each plot 1 m x 1 m. The object of the study was in the form of weeds in the sample plots that were given different treatments, namely using a single herbicide using a Kenfosat herbicide with the active ingredient isopropyl amine glyphosate with a dose of 2 liters/ha in block 73B and a mixed herbicide consisting of a Kenfosat herbicide with the active ingredient isopropyl amine glyphosate + Mitsufuron herbicide with the active ingredient methyl metsulfuron + agristick with the active ingredient alkyllaril polyglycol ether with a dose of 2 liters/ha + 0 each, 075 gr/ha + 0.1 liters/ha in block 68A. The results showed that the types of weeds that grew in the oil palm disk area were broad-leaved weeds such as Ageratum conyzoides, Asystasia intrusa, Clidemia hirta, Phyllanthus urinaria and narrow-leaved weeds such as Setaria plicata. Based on the content of the active ingredient, the most effective herbicide in controlling weeds in the oil palm disc area is a mixed herbicide because it is able to kill weeds completely (100%) on the 15th day after the herbicide application.